Communication subjective assessments of patients undergoing compulsory treatment with the severity of negative symptoms and cognitive functioning level - Kabanov T.N.; Kazakovtsev B.A. (Психология и право, 2015)
The article presents the results of studies on the relationship of subjective assessments of the mentally ill with the severity of negative symptoms and cognitive functioning level. The features of patients perception of various aspects of compulsory treatment and subjective satisfaction with treatment. In a study of 94 male patients with a diagnosis of organic mental disorder and schizophrenia was used diagnostic system, consisting of patopsihologicheskogo study, formal survey map, the scale of assessment of negative symptoms SANS, questionnaire symptom levels SCL-90, self-existing problems, as well as - in Test authoring tool sheet to treatment and hospital stay (VG Bulygin, Kabanov, TN, 2011). The differences in subjective assessments of aspects of compulsory treatment and social functioning of patients with varying degrees of severity of negative symptoms and dependence of subjective assessments of the level of cognitive functioning.